DARI LAYAR KE LARIS MANIS : SINERGI LIVE STREAMING DAN VIRAL MARKETING DALAM MEMBERDAYAKAN UMKM WISATA BERBASIS KOMUNITAS DI SULAWESI SELATAN - Erwin Erwin; Yuyun Karystin Meilisa Suade; Monalisa Monalisa; Novika Ayu Triany (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
Tourism in South Sulawesi holds significant potential, yet Micro, Small, and Medium Enterprises (MSMEs) within the sector frequently encounter challenges in expanding market reach and enhancing competitiveness. This study investigates the contributions of live streaming, viral marketing, and local community co-creation to the competitiveness of tourism MSMEs. This descriptive quantitative study involved 162 tourism MSME actors in South Sulawesi who actively utilize social media, have engaged in live streaming, leveraged viral moments for promotion, and collaborated with local communities. Data were collected via a 5-point Likert scale questionnaire and subsequently analyzed using PLS-SEM, processed with WarpPLS Version 8.0. The findings indicate that while live streaming does not directly enhance MSME competitiveness, it exerts a robust and positive influence on local community co-creation. Conversely, viral marketing demonstrably and significantly impacts both MSME competitiveness and local community co-creation. Most notably, local community co-creation directly and highly effectively boosts MSME competitiveness, also serving as a crucial mediator that transforms the effects of both live streaming and viral marketing into substantial gains in MSME competitiveness. These findings underscore the pivotal role of co-creation in converting the impact of digital marketing into a distinct competitive advantage.